2017
DOI: 10.1136/emermed-2016-206148
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Manchester Acute Coronary Syndromes (MACS) decision rule to safely reduce unnecessary hospital admissions: a pilot randomised controlled trial

Abstract: BackgroundObservational studies suggest that the Manchester Acute Coronary Syndromes (MACS) decision rule can effectively ‘rule out’ and ‘rule in’ acute coronary syndromes (ACS) following a single blood test. In a pilot randomised controlled trial, we aimed to determine whether a large trial is feasible.MethodsPatients presenting to two EDs with suspected cardiac chest pain were randomised to receive care guided by the MACS decision rule (intervention group) or standard care (controls). The primary efficacy ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Integration of clinical judgement or a validated clinical score such as the GRACE, TIMI, HEART, modified Goldman Score, MACS clinical decision rule, EDACS and Vancouver Chest Pain Algorithm and North American Chest Pain Rule further improve NPV yielding NPV between 98.1% to 100% and 98.4% to 100% when cTn and hs-cTn assays were used, respectively 40. Although, 2015 ESC guidelines10 discourage routine invasive strategy in low risk patients and rather recommend discharge following risk stratification, and a pre-discharge or post-discharge stress imaging test to decide on a selective invasive strategy, evidence from randomised trials to endorse these recommendations is sparse 20–22. The Manchester Acute Coronary Syndrome (MACS)-Pilot study20 enrolled 138 patients with suspected cardiac chest pain who were randomised to receive care guided by the MACS decision rule or standard care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integration of clinical judgement or a validated clinical score such as the GRACE, TIMI, HEART, modified Goldman Score, MACS clinical decision rule, EDACS and Vancouver Chest Pain Algorithm and North American Chest Pain Rule further improve NPV yielding NPV between 98.1% to 100% and 98.4% to 100% when cTn and hs-cTn assays were used, respectively 40. Although, 2015 ESC guidelines10 discourage routine invasive strategy in low risk patients and rather recommend discharge following risk stratification, and a pre-discharge or post-discharge stress imaging test to decide on a selective invasive strategy, evidence from randomised trials to endorse these recommendations is sparse 20–22. The Manchester Acute Coronary Syndrome (MACS)-Pilot study20 enrolled 138 patients with suspected cardiac chest pain who were randomised to receive care guided by the MACS decision rule or standard care.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the patients who retrospectively fulfilled early rule-out criteria were kept in hospital and neither medical measures nor non-cardiac diagnoses are reported. Only few interventional clinical trials evaluated the safety of a randomised allocation to early discharge versus conventional care in patients at low20 21 or low-to-intermediate high risk 22. The Biomarkers-in-Cardiology 8 (BIC-8) trial22 tested the utility of a dual biomarker strategy using normal cTn or hs-cTn values, that is below the upper limit of normal, mainly the 99 th percentile, together with normal Copeptin values below the 95 th percentile (<10 pmol/L) to identify candidates for direct early discharge from the ED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test characteristics of H-FABP versus hs-Tn in those presenting to ED with CP, stratified by time to symptom onset. recent pilot RCT found that the MACS rule enabled 26% patients to be successfully discharged from the ED within 4 h with no incident AMI in 30 days among those discharged [63]. Similarly, an analysis of a singlecenter arm of the multi-center ADAPT study found that when combined with EKG, H-FABP orhs-Tn alone had unacceptably low sensitivity [64].…”
Section: H-fabp In the Era Of High-sensitivity Troponin (Hs-tn)mentioning
confidence: 99%
“…Use of the decision aid led to an increase in the proportion of patients safely discharged from the ED within 4 h of arrival (adjusted odds ratio 5.5, 95% CI 1.7–17.1, p = 0.004), although the analysis was underpowered to specifically study the incidence of MACE in the ‘very low risk’ group. 37 …”
Section: Towards Acs Diagnosis Version 20mentioning
confidence: 99%